2013
DOI: 10.1080/1612197x.2013.830431
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to drop-out of youth soccer: A test of the basic needs theory among European youth from five countries

Abstract: A test of the basic needs theory among European youth from five countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
82
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 43 publications
22
82
0
14
Order By: Relevance
“…Nielsen et al (2014) compared the experiences and motivation associated with football and spinning and found that participating in a team game satisfied the basic psychological needs for feelings of competence and relatedness to others more than individual fitness activities in a male sample. This finding is supported by studies linking psychological need satisfaction to motivation (Jõesaar, Hein, & Hagger, 2011) and enjoyment (Quested, et al, 2013), as well as social affiliation (Wallhead, Garn, & Vidoni, 2013) to enjoyment and peer support to motivation (Griffith, King, & Allen, 2013). Therefore, higher satisfaction of the basic psychological needs is one possible cause of the higher levels of intrinsic motivation observed among the floorball participants compared to the spinning participants.…”
Section: Discussionsupporting
confidence: 72%
“…Nielsen et al (2014) compared the experiences and motivation associated with football and spinning and found that participating in a team game satisfied the basic psychological needs for feelings of competence and relatedness to others more than individual fitness activities in a male sample. This finding is supported by studies linking psychological need satisfaction to motivation (Jõesaar, Hein, & Hagger, 2011) and enjoyment (Quested, et al, 2013), as well as social affiliation (Wallhead, Garn, & Vidoni, 2013) to enjoyment and peer support to motivation (Griffith, King, & Allen, 2013). Therefore, higher satisfaction of the basic psychological needs is one possible cause of the higher levels of intrinsic motivation observed among the floorball participants compared to the spinning participants.…”
Section: Discussionsupporting
confidence: 72%
“…This is refl ected, for example, in studies already off ering comprehensive theories and integrated constructs (Deci & Ryan, 1985Klint & Weiss, 1986;Leonard, 1998;, 2007Ntoumanis, 2012;Quested et al, 2013). Others authors try to search for solutions and address specifi c motives which infl uence dropouts of OPA such as Orlick (1974), LeBlanc and Dickson (1997), Jõesaar, Hein and Hagger (2012) or again Quested et al (2013). However, quantitative data per se cannot apparently cover the variety of variables and the context.…”
Section: Introductionmentioning
confidence: 99%
“…They evaluate whether the sport makes them happy, a credit attributed to the sport by themselves or by their reference groups, or consider what they gain or lose by do-ing sports, or whether they are made to give up OPA because of reasons which go beyond their capacity to solve them satisfactorily (injuries, increased costs, or time confl icts). This is refl ected, for example, in studies already off ering comprehensive theories and integrated constructs (Deci & Ryan, 1985Klint & Weiss, 1986;Leonard, 1998;, 2007Ntoumanis, 2012;Quested et al, 2013). Others authors try to search for solutions and address specifi c motives which infl uence dropouts of OPA such as Orlick (1974), LeBlanc and Dickson (1997), Jõesaar, Hein and Hagger (2012) or again Quested et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been based on earlier theories and models, such as the Health Belief Model (Rosenstock, 1966) and the Theory of Planned Behaviour (Ajzen, 1991) yet not all research in this area has been carried out within such frameworks. For instance Quested, Ntoumanis and Viladrich (2013) examined dropout of youth soccer across five European countries employing a basic psychological needs theory, and Guzman and Kingston (2012) looked at sport dropout and motivation as a function of age and gender based on self determination theory. Yet, as mentioned previously, much research has been conducted to investigate dropout in sport outside of any particular frameworks or models.…”
Section: Introductionmentioning
confidence: 99%